KETERKAITAN REGIONAL DALAM SMART TOURISM DI KAWASAN SARBAGITA - Harmaen; Djunaedi, Achmad (Jurusan Teknik Perencanaan Wilayah dan Kota, Fakultas Sains dan Teknologi, Universitas Islam Negeri Alauddin Makassar, 2025)
The concept of smart tourism is commonly applied to cities or towns, which use information and communication technology (ICT) to improve efficiency, traveler experience, and tourism destination management. However, this concept is often considered less relevant for regional areas with different characteristics. In addition, tourism today is no longer focused on a single location, but rather encourages a trend of development based on inter-regional linkages. In Sarbagita, Denpasar and Badung's tourism GRDP is higher, supported by a smart city masterplan, while Gianyar and Tabanan do not yet have one. This research aims to describe regional linkages in smart tourism in the Sarbagita Region. Through a qualitative approach, this research makes the theoretical framework a guide to see inter-regional linkages in smart tourism. The findings are inter-regional linkages in smart tourism in the Sarbagita Region, at the level of strategy, planning, and tourism policy, there are indirect linkages through strategy and promotion. At the service development level, the role of the private sector supports linkages through e-ticketing, QR codes, and tour packages. Tourism promotion linkages can be seen in government initiatives, such as participation in tourism exhibitions and the Bali regional tourism website. Accessibility is adequate but still limited to the local level.